Determination of the coefficient psi2 to define long-term effects on concrete elements under variable load - Nakov, D., Markovski, G., Mark, P., Arangjelovski, T. (University Ss. Cyril and Methodius, Faculty of Civil Engineering-Skopje, 2015)
During the past 12 years, research project regarding time-dependent behavior of concrete elements is ongoing continuously at the Faculty of Civil engineering in Skopje. Experiments were performed on different types of concrete: prestressed, normal and high strength and steel fibre reinforced concrete, with various loading histories. The time-dependent changes in strains, deflections and crack widths were observed in a period of 400 days. This paper presents the effects of variable load on time-dependent behaviour of different types of concrete elements and proposes methodology for determination of coefficient ψ2.
Keywords: coefficient ψ2, experiment, long-term variable load